Analysis of Strategy and Communication Approach in The Green Campaign of Luxcrime x Seven Clean Seas on Social Media (Tiktok & Instagram) - Devany Dwi Putri Halim; Athaya Almira Nur Azzahra (LSPR Institute of Communication & Business, 2026)
The growing public concern for environmental issues has encouraged beauty brands to adopt sustainable and socially responsible marketing approaches. This study examines the collaborative campaign between Luxcrime and the environmental organization Seven Clean Seas, which promoted ocean conservation through the purchase of selected beauty products. The study aims to analyze the digital communication strategies used in the campaign and to explore how public-figure involvement and consumer engagement contributed to shaping Luxcrime’s brand value. A qualitative case study method was applied, drawing on social media content observation, campaign documentation, and in-depth interviews with key stakeholders. The findings show that the campaign integrated emotional messaging, strong visual identity, and calls to action that resonated with younger audiences on Instagram and TikTok. Influencer participation, particularly when done voluntarily, enhanced trust and strengthened the perception of Luxcrime as a socially responsible brand. The analysis also highlights how controlled communication channels allowed Luxcrime to maintain message clarity while collaboration with an environmental NGO added credibility to the sustainability claims. These elements collectively supported the development of positive brand associations and consumer appreciation toward the campaign. The study provides insights into how visual storytelling, authenticity, and strategic partnerships contribute to the effectiveness of digital green marketing campaigns.